Tracing the Traces of Roman Panji & Its Influence on Mask Art in Bobung, Yogyakarta, Indonesia - Slamet Subiyantoro; Susilaningsih Susilaningsih; Favorita Kurwidaria; Dimas Fahrudin; Yasin Surya Wijaya (Budapest International Research and Critics University, 2021)
This study aims to explore the history of the journey of the Panji story and find out its influence on mask art in Bobung, Gunung Kidul, Yogyakarta. This study uses a qualitative descriptive approach with a historical perspective. Data sourced from informants, places & events, and documents/archives collected using in-depth interviews, participatory observation, and content analysis techniques. The validity of the data was tested with the technique of reviewing informants and triangulation of data sources. Data were analyzed using an interactive model consisting of data reduction procedures, data display, and verification or drawing conclusions. The results of the study show that Roman Panji became the original hero of the archipelago, especially Java, which experienced a peak of popularity during the golden age of the Majapahit Kingdom, namely the middle of the VIII century. Panji became a novel that spread widely covering the archipelago to Southeast Asia. The end of the VIII century until the XV century Panji Mask became a popular show where King Hayam Wuruk was famous as a mask dancer and the main dancer in racket performances. Wayang Beber is a wayang art which in the show brings the story of Panji. Wayang Beber art is in Pacitan, East Java, but also in Karangmojo, Gunung Kidul Yogyakarta. Mbah Karso was the first mask master who was influenced by the Panji story and created the masks that still exist and thrive in Bobung, Gunung Kidul, Yogyakarta. In the current era, Panji Masks have been commodified into handicraft products with economic and tourism value.